Organ tuition for beginners without previous keyboard skills: a critical evaluation of four published methods against the background of initial piano tuition and general organ pedagogy - Steyl, Marian (Stellenbosch : Stellenbosch University, 2018)
Thesis (MMus)--Stellenbosch University, 2018.